The Effect of Commonality on Safety Stock in a Simple Inventory Model - Baker, Kenneth R.; Magazine, Michael J.; Nuttle, Henry L. W. (Management Science, 1986)
We examine the effects of component commonality on optimal safety stock levels in a two-product, two-level inventory model. The criterion is to minimize system safety stock subject to a service level constraint. Although our model is specialized, its analysis provides insights not available in other multilevel inventory models.